Identity Politics and Threats to Religious Pluralism in Bukittinggi - Endrizal, Endrizal; Emzia Fajri (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This study examined the issue of identity politics and the threat of pluralism in Bukittinggi, West Sumatra. The people of Bukittinggi, West Sumatra consisting of various ethnicities, tribes, races and cultures have been able to live with a spirit of pluralism and tolerance. Lately, the spirit of pluralism that has been run by the people of Bukittinggi, West Sumatra began to erode along with the strengthening of identity politics. The prominence of tribal, religious, racial and cultural identities becomes a serious problem in a plural society, because, the spirit of highlighting tribal, racial, cultural and religious identities excessively leads to claims of truth and the assumption that their tribes, races, religions and cultures are superior to cultures, races, tribes and religions outside their groups. In collecting data, this study uses qualitative methods. The research stages carried out are literature studies, observations, documentation, and interviews. The research will be guided by social theories such as identity politics and pluralism. The finding of this research is the strengthening of identity politics in Bukittinggi related to religious issues. Politically, religions outside of Islam are limited. This religious identity is further strengthened by the emergence of many religious groups in the midst of the people of Bukittinggi, West Sumatra. like Islamic organizations that massively bergeriliya in carrying out its mission to Islamize the entire community of west Sumatra. The movements carried out by islamic organizations seem to be strengthened by ethnicity (tribal), in the form of customs of the people of Bukittinggi, West Sumatra which is famous for its integration of customs and religions. Indirectly religion outside the religion of Islam its existence is limited in Bukittinggi, West Sumatra.